Information technologies specialists’ professional readiness: structure development - Svetlana G. Menshenina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Development of readiness for professional work is a topical issue due to increasing requirements for University graduates. The article considers development future information security specialists readiness for professional work. Literature review helped the author to work out his own definition of readiness for professional work and develop a structure of readiness for information security specialists’ leading activity - analytical, which consists of four components. The correlation between components and functions, specificity, leading activity and instrument of professional work of information security specialists is defined. The article contains an assumption that graduate’s readiness for professional work is defined by the level of its components development.